Do commercial acccounts and the tax base have to be aligned? - Aguiar, Nina (2011)
This paper intends to discuss some aspects considered relevant for the taxation-accounting formal link issue. The first aspect treated, given the importance it has been given in the debate, concerns the alleged divergence of purposes between taxation and accounting. We sustain that opposing these two terms is not a valid approach and leads to a falsification. Instead of comparing financial/commercial accounting and taxation purposes, it is necessary to compare the sought characteristics of financial mensuration in both fields. On the taxation field, mensuration features must above all meet the ability to pay principle. Until now, the characteristics of commercial accounting mensuration were clearly defined, because commercial accounting purposes were relatively well defined as well. The commercial accounting mensuration characteristics matched taxation needs perfectly. In contrast, commercial accounting norms structure, with their large discretional powers, did not fit taxation needs, namely the legality principle. The formal link to the commercial balance sheet is precisely what allows overcoming that structural incompatibility. In the meantime, accounting regulation in the European context changed, with the legalization of IFRS. Looking at the new normative context, we must conclude that the prudence principle was basically preserved, and even the realization criterion was maintained to a great extent. The fair value criterion does not oppose realization. The fair value criterion fits a SHS comprehensive concept of income; it poses only a liquidity problem, but there is no fundamental incompatibility between fair value and ability to pay. But apart from the compatibility of income measurement for commercial and tax purposes, the relationship between taxation and accounting cannot be validly discussed if we don’t analyse the tax legal foundations of that relationship. Those foundations lie, in the first place, on the ability to pay principle, which demands the tax to be levied on real income. The second foundation for that formal link resides on the proof function guaranteed by the commercial balance sheet. These two foundations are still completely valid and irreplaceable, within the corporate tax. Abolishing the formal link between taxation and accounting entails eliminating the tax law referring to commercial law, and creating instead a set of tax rules for the calculation of the tax base, based on presumptions, i.e, entails going back to taxing a deemed income. But even when income calculated on fair value seems to fit ability to pay, a great concern has been expressed about taxing fair value-income. So this paper also tries to show how a formal link system disposes of a variety of solutions to deal with the fair value criterion, keeping “formal link” intact. Recent experience on the adaptation of corporate tax codes to an IFRS-based accounting show that a formal link is compatible with a complete inclusion of fair value variations in taxable income (Italy), an inclusion of “realized” fair value variations (Spain) and a selective inclusion/exclusion of certain fair value variations (Portugal). So commercial income and taxable income really do not have to be aligned, as a condition to maintain a formal link between the two.